Artistic Features in Children’s Literature - hadli, laldja (El Omda in Linguistics and Discourse Analysis, 2023)
Despite its simplicity and ease, Children’s Literature, shall notbe consideredas a microcosm of adult literature, because it has its distinctive characteristics preceded by the nature of children themselves. In other words, they differ from adults not only in the growthvariable, but in the direction of that growth as well. Their needs and their characteristics, in particular, differ in trajectory from what features distinguishing adults. Accordingly, not every literary work presented to adults becomes, once simplified, literature for children, as it must correspond to their abilities and stages of mental, psychological and social development.Hence,children’s literature is characterized by expressive and other aesthetic characteristics capable of keeping pace with the child’s desire to know more and meet his needs for pleasure.